PRODUCTIVITY AND QUALITY INDICATORS OF INDETERMINANT TOMATO HYBRIDS - Sievidov, V. P.; Sievidov , I. V. (Scientific Progress & Innovations, 2022)
One of the main areas of intensification of the vegetable growing industry is the level of manufacturability in the process of caring for crops and harvesting, which, among other things, depends on the biological potential of hybrids. Given the constant increase in the range of tomatoes available in Ukraine, certain aspects of substantiating the features of the formation of the crop of indeterminate tomato hybrids in terms of the formation of an effective technology for growing tomatoes in spring film greenhouses remain insufficiently studied and quite relevant at the present stage. The purpose of the research was to evaluate and select the yield of tomato hybrids for growing in film greenhouses. Experimental studies were carried out for five years in a field crop rotation. The experimental site is located in the eastern part of the left-bank Forest-Steppe of Ukraine, on the territory of the Kharkiv district of the Kharkiv region. The following F1 hybrids were studied in the experiment: Berberana, Panekra, Matias, Belfort, Tobolsk, Zulfiya, Signora, Ronda, Makhitos, Bostina, Alamina, Yarina, Toivo. The conducted studies showed that the biometric characteristics of tomato plants significantly depended on the hybrid under study. The influence of the hybrid genotype on the level of productivity of modern tomato hybrids when grown in film greenhouses was determined. In the course of the experiment, it was determined that F1 hybrids of Signora, Belfort and Matias were distinguished by a set of biometric indicators, which, when grown in a spring film greenhouse, develop better and have better ratios of vegetative mass, plant height, leaf surface area and average fruit weight. Based on the results of the field experiment, it was shown that the Berberana F1 hybrid plants (control) formed an average yield during the growing season at the level of 15.5 kg/m2. The highest yield was recorded in the Signora F1 hybrid ‒ 16.9 kg/m2, which is 1.4 kg/m2 more than the control. The Matias F1 hybrid also showed itself well, the yield of which was 16.4 kg/m2, and was 0.9 kg/m2 more than the control. It was determined that F1 hybrids Mathias and Signora, which are characterized by the best growth and development of plants and show the highest yield among the studied ones, turned out to be the best for growing in film greenhouses in the spring-summer crop change.